POLA ASUH KELUARGA DAN PERILAKU BULLIYING DI SEKOLAH MENENGAH KEJURUAN - Anisa Amiliana Angin; Kusuma, Yudha Laga Hadi; Atikah Fatmawati (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Bullying is the intentional and conscious desire to hurt another person and put them under pressure. This study aimed to analyze the relationship between family upbringing and bullying behaviour in adolescents at SMKN 1 Dlanggu Mojokerto. This study used a correlational research design with a cross-sectional approach. The population in this study were 967 students in grades 10 and 11 at SMK N 1 Dlanggu Mojokerto. This study used 212 respondents as a sample using the Proportionate Stratified Random Sampling technique. The instrument used in this study was a parenting questionnaire and Adolescent Peer Relations Instrument – ​​Bullying (APRI-BT). The results showed that almost half of the respondents had authoritarian parenting styles (38.7%), and almost half tended to be victims of bullying (42.0%). The chi-square test results obtained a p–value of 0.314, meaning there is no relationship between parenting style and bullying behaviour in adolescents at SMKN 1 Dlanggu Mojokerto. Factors that influence bullying are family factors, peers, media influence, school factors, and social environmental conditions factor. Increasing understanding of adolescent bullying behaviour and parenting by parents is essential. This reduces the occurrence of bullying behaviour among adolescents.